Kajian tentang perbedaan umpan pancing Noru terhadap hasil tangkapan - Adhitya Teguh Prasetyo Saselah Aditya; Ivor Lembondorong Labaro; Alfret Luasunaung; Mariana Elizabeth Kayadoe; Lefrand Manoppo (Universitas Sam Ratulangi, 2023)
The aims of this study to analyze the differences the catch of the “noru” fishing gear using nipple rubber and silk fibre lures, as well as to identify the catches obtained. Small pelagic fish are organisms that live in the open sea, separated from the bottom of the water and towards the surface layer. These fish generally like to be in groups, both with their groups and with other types of fish. Also have positive phototaxis (attracted to light) and are attracted to floating objects. Bait is an important factor in increasing the effectiveness of catching small pelagic fish using “noru” fishing gear or hand lines. The interest of artifial bait in this fishing gear has several criteria, including: the shape of the bait must be similar to shape of food, easy visible because of the color and the bait looks alive when the gear is operated. The results of the study showed that noru (hand line) to used nipple rubber lures gave more catches compared to using silk fibre lures. From the catch, there were 4 species of fish caught using nipple rubber lures, namely yellowstrip scad, bigeye scad, trevally and Indian mackerel while using silk fiber lures 2 species of fish, namely yellowstrip scad and bigeye scad.